2018
DOI: 10.1186/s13104-018-3737-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Escherichia coli isolated from ice cube production sites

Abstract: ObjectiveThe prevalence of Escherichia coli including from ice cubes in Indonesia is quite high. Unfortunately, little is known about the genetic diversity of E. coli from ice cube production site. Genotypic variation in E. coli populations is a major barrier to control public health risk associated with foodborne pathogen. The aims of this study were to analyze the genotypic diversity of E. coli strains isolated from various samples in order to determine the genetic relationship between those strains. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(30 reference statements)
0
1
1
1
Order By: Relevance
“…3) at 95 per cent similarity cut-off value and exhibited genetic heterogeneity, but Jonas et al [63] reported isolates with similarities above 70-80% which were eventually assigned to the same genotypes. Another study by Pusparini et al [64] reported several unique clusters of ERIC in E. coli strains isolated from ice cube production sites which showed genetic diversity with 50 per cent cut-off value which is in contrary to the similarity cut-off value generated in this present study. On the basis of ERIC-PCR ngerprint, some of the isolates included in our study were genetically diverse.…”
Section: Discussioncontrasting
confidence: 99%
“…3) at 95 per cent similarity cut-off value and exhibited genetic heterogeneity, but Jonas et al [63] reported isolates with similarities above 70-80% which were eventually assigned to the same genotypes. Another study by Pusparini et al [64] reported several unique clusters of ERIC in E. coli strains isolated from ice cube production sites which showed genetic diversity with 50 per cent cut-off value which is in contrary to the similarity cut-off value generated in this present study. On the basis of ERIC-PCR ngerprint, some of the isolates included in our study were genetically diverse.…”
Section: Discussioncontrasting
confidence: 99%
“…In the lack of appropriate software, the band patterns generated by REP-PCR were assessed visually. The binary matrix was built based on the absence or presence of each band (coded 0 or 1, respectively) ( Pusparini et al, 2018 ). Phylogenetic tree based on binary matrix was constructed by the free online service at http://insilico.ehu.eus/dice_upgma/ .…”
Section: Methodsmentioning
confidence: 99%
“…Pohon filogenetik hasil ERIC PCR menunjukkan kekerabatan isolat Vibrio dari air, feses, hepatopankreas, udang sehat dan udang EHP. Clustering pada pohon filogenetik dilakukan berdasarkan tingkat kemiripan 50% (0.5 similarity) (Pusparini et al, 2018).…”
Section: Tabelunclassified